Cave fragmentation in a cave-to-mill context at the New Afton mine Part II: implications to mill performance. Issue 3 (3rd July 2018) - Nadolski, Stefan; O'Hara, Christopher; Klein, Bern; Elmo, Davide; Hart, Craig J. R.
Abstract: The productivity of milling circuits is sensitive to the size of mill feed. Uncertainty about the size of caved ore presents unique challenges to forecasting and controlling mill throughput rates. Part I of this paper showed how fragmentation size and hang-up frequency relate to geology, proximity of drawpoints to the cave boundary and the height of draw at the New Afton mine. The second part, presented here, investigates the impact of varying caved fragment size on mill performance. Analysis of historical mine and mill data showed that mill feed size and subsequently mill throughput are sensitive to the areas being mucked within the cave. Fragmentation measurements of drawpoint muck, comminution tests and calibrated mill models were used to assess the impact of variations in feed size and hardness on New Afton mill performance. Image-based size analyses of drawpoint muck and comminution tests showed that coarser material generally contained harder rock.